ASSA14-06-01 Is Long-term Warfarin Therapy Necessary in Patients With Mitral Bioprosthetic Valves Plus Atrial Fibrillation?. (1st December 2014) - Zhang, L; Jiang, S; Ren, C; Xiao, C; Wang, R; Gao, C
Abstract : Background: Thromboembolism is a major complication after bioprosthectic mitral valve replacement (BMVR) in patients with atrial fibrillation (AF). The antithrombotic therapy in current guideline lacks evidence. Objectives: A retrospective study was conducted to investigate the efficacy of long-term warfarin or aspirin therapy in patients with AF after BMVR. Methods: A total of 126 patients presenting with persistent AF underwent BMVR were given anticoagulation therapy with warfarin for 3 months, following warfarin or aspirin therapy according to the surgeon's preference. The patients were followed up by telephone or mail for postoperative condition, cerebravascular and bleeding events. Results: 117 (92.9%) patient's detailed data was available, of which 5 died within 3 months for heart failure, 1 for cerebral infarction and 1 for sudden death. The remaining 112 patients were divided into two groups: Aspirin group (61 patients) and Warfarin group (51 patients). Two groups had similar incidence of cerebral infarction or transient ischaemic attack (TIA) (11.8% vs 14.8%, p = 0.644) and bleeding events (11.8% vs 6.6%, p = 0.336). Each group had one intracranial haemorrhage. 11 patients were dead after three months after surgery, 4 (7.8%) in the Warfarin group and 7 (11.5%) in Aspirin group (p = 0.520 by fisher exact test, p = 0.952 by Kaplan–Meier survival analysis). Univariate analysis demonstrated diabetes, prior cerebral infarction, concomitant CABG and tricuspid valve repair and no left atrial appendage obliteration as risk factors for cerebral infarction and TIA. Conclusions: In current era in china, antithrombotic therapy with warfarin or aspirin had no significant different impact on long-term prognosis after 3 months anticoagulation with warfarin in patients with AF undergoing BMVR.